Dilemmas of Security: The State, Local Agency, and the Czechoslovak-Hungarian Boundary Commission, 1921–25. (1st May 2018) - Haslinger, Peter
Abstract : In a memorandum presented to the Hungarian-Czechoslovak Boundary Commission on 23 February 1922 by the inhabitants of the southern Slovak town of Viškovce (Hungarian: Ipolyvisk), the twenty-five signatories requested "humbly for consideration and well-meaning settlement of the following concern." The municipality was bordered on three sides by the Ipeľ (Hungarian: Ipoly) River, but had been cut off from the only usable road by the border, making communication extremely difficult. In winter and at high water in the spring and autumn, the place was "completely cut off from the outside world." For three years, they had observed how provisional boundaries were continuously redrawn, and bore the brunt of these changes. The inhabitants said that all alternative routes had become inaccessible during that time and the center of Šahy (Hungarian: Ipolyság), which was just ten kilometers away, had become extremely difficult to reach even in urgent cases. Thus, they requested that the only existing road "be opened to us as quickly as possible and our traffic given back to us."